The Meter of the Ophni and Phineas Insertion in Piers Plowman - Eric Weiskott (Studia Metrica et Poetica, 2022)
The C version of Piers Plowman has yet to earn much attention from metrists relative to the outgrowth of research into fourteenth-century alliterative meter since 1986. Langland’s relationship to metrical tradition is idiosyncratic, a judgment that involves both this author’s divergence from conventions characteristic of other alliterative poems and the recognizability of his own metrical habitus across his career. Scansion of an inconsistently alliterating passage new in C (Prol.95–124) illustrates in miniature the unusual problems thrown up by Langland’s metrical practice and suggests that his metrical signature persisted over the years of his writing life. The Ophni and Phineas insertion is of special interest because it has been thought an unfinished draft.